If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 4(x + -4) + -1(x + -8) Reorder the terms: 13 = 4(-4 + x) + -1(x + -8) 13 = (-4 * 4 + x * 4) + -1(x + -8) 13 = (-16 + 4x) + -1(x + -8) Reorder the terms: 13 = -16 + 4x + -1(-8 + x) 13 = -16 + 4x + (-8 * -1 + x * -1) 13 = -16 + 4x + (8 + -1x) Reorder the terms: 13 = -16 + 8 + 4x + -1x Combine like terms: -16 + 8 = -8 13 = -8 + 4x + -1x Combine like terms: 4x + -1x = 3x 13 = -8 + 3x Solving 13 = -8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 13 + -3x = -8 + 3x + -3x Combine like terms: 3x + -3x = 0 13 + -3x = -8 + 0 13 + -3x = -8 Add '-13' to each side of the equation. 13 + -13 + -3x = -8 + -13 Combine like terms: 13 + -13 = 0 0 + -3x = -8 + -13 -3x = -8 + -13 Combine like terms: -8 + -13 = -21 -3x = -21 Divide each side by '-3'. x = 7 Simplifying x = 7
| 28x^3-21x^2-7x=0 | | 18=-3x-4 | | 20x+30+5x+40=570 | | 20x+30+5x+40=574 | | -7-3x=-12 | | 10cos^2x-11cosx-6=0 | | 20x+30+5x+40=576 | | 20x+30+5x+40=581 | | 20x+30+5x+40=582 | | -3=-4-11x | | 20x+30+5x+40=579 | | -6x-1=-14 | | 20x+30+5x+40=580 | | d+32=108 | | 5y-9=13y+7 | | 20x+30+5x+40=600 | | -24x^3-8x^2=0 | | 20x+30+5x+40=700 | | 7=5-3x | | 4/9=x/15 | | 5m=250 | | 20x+30+5x+40=220 | | 12y+35=3 | | 5-2x=-4 | | 3x^2-17x+12=y | | 3/2X+1/2X | | 3x-8x+7=3x-8+11x | | 11=-8x+4 | | 6x-(4x-3)=11 | | -3x+4=-3 | | y=3x^2-24x+46 | | 7=3x+2 |